Proceedings of the 7th Workshop on Multimedia and Security 2005
DOI: 10.1145/1073170.1073190
|View full text |Cite
|
Sign up to set email alerts
|

Robust non-interactive zero-knowledge watermarking scheme against cheating prover

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There is no need for two parties to communicate with each other in NIZKP, except sending one data set from the prover to the verifier. [21][22][23] It can also be adapted to a required security level so that the greater the number of different challenges, the higher the security level of the verifier. 24 The efficiency of non-interactive is encouraging owning to no interaction with the verifier.…”
Section: Related Workmentioning
confidence: 99%
“…There is no need for two parties to communicate with each other in NIZKP, except sending one data set from the prover to the verifier. [21][22][23] It can also be adapted to a required security level so that the greater the number of different challenges, the higher the security level of the verifier. 24 The efficiency of non-interactive is encouraging owning to no interaction with the verifier.…”
Section: Related Workmentioning
confidence: 99%
“…Yu and Lu [12] presented a detector for zero knowledge watermark detection. Their scheme is resistant to ambiguity attacks by incorporating a one-way function based on the difficulty in finding Hamiltonian cycles in graphs.…”
Section: Related Workmentioning
confidence: 99%
“…They used the cryptographically secure pseudo-random number generator and required that the watermarks are all generated from the generator with the same seed but with different indices associated with different works. However, similarly to Yu and Lu's method [12], their security is not sufficient to prevent ambiguity attacks, because there is not a great correlation between the secret sequence (watermark) and the original image. We also found that the ZKWD protocols presented so far are not established based on a robust watermarking scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Adelsbach et al [3] and Craver [9] proposed the use of zeroknowledge proofs in watermarking. Yu and Lu proposed a similar method based on a specially designed robust watermarking scheme [23]. In most cases, we can consider the watermark as the secret, and the property to be proved is the existence of the watermark.…”
Section: Related Workmentioning
confidence: 99%
“…It was pointed out in [2,1] that a watermarking scheme cannot be noninvertible if the false alarm is high. Yu and Lu claimed that their proposed zero-knowledge watermark detector [23] is resistant to ambiguity attacks by incorporating a one-way function based on the difficulty in finding Hamiltonian cycles in graphs. However, it seems that their security proof is not sufficient, since the difficulty of inverting the one-way function does not imply the resistance against ambiguity attacks.…”
Section: Related Workmentioning
confidence: 99%